Hedonic perception of odors in children aged 5-8 years is similar across 18 countries: Preliminary data - Oleszkiewicz, A; Schriever, V A; Valder, C; Agosin, E; Altundag, A; Avni, H; Cao Van, H; Cornejo, C; Fishman, G; Guarneros, M; Gupta, N; Kamel, R; et al. (International journal of pediatric otorhinolaryngology, 2022)
OBJECTIVE: Olfactory preference emerges very early in life, and the sense of smell in children rapidly develops until the second decade of life. It is still unclear whether hedonic perception of odors is shared in children inhabiting different regions of the globe. METHODS: Five-hundred ten healthy children (N = 510; ngirls = 256; nboys = 254) aged from 5 to 8 years from 18 countries rated the pleasantness of 17 odors. RESULTS: The hedonic perception of odors in children aged between 5 and 8 years was rather consistent across 18 countries and mainly driven by the qualities of an odor and the overall ability of children to label odorants. CONCLUSION: Conclusions from this study, being a secondary analysis, are limited to the presented set of odors that were initially selected for the development of U-Sniff test and present null findings for the cross-cultural variability in hedonic perception of odors across 18 countries. These two major issues should be addressed in the future to either contradict or replicate the results presented herewith. This research lays fundament for posing further research questions about the developmental aspects of hedonic perception of odors and opens a new door for investigating cross-cultural differences in chemosensory perception of children.
Keywords: Odorants; Emotions; Female; dítě; předškolní dítě; předběžné údaje; Hedonic perception; Perception; ženské pohlaví; Olfaction; Children; emoce; Smell; percepce; lidé; odoranty; Psychophysiology; Preliminary Data; Male; Child, Preschool; Odor identification; Child; mužské pohlaví; čich; Humans